Efficacy of Antiseizure Medications in Wolf–Hirschhorn Syndrome - Horiguchi, Ayumi; Koichihara, Reiko; Kikuchi, Kenjiro; Nonoyama, Hazuki; Daida, Atsuro; Oba, Daiju; Hirata, Yuko; Matsuura, Ryuki; Ohashi, Hirofumi; Hamano, Shin-ichiro (Neuropediatrics, 2023)
Wolf–Hirschhorn syndrome (WHS) is caused by deletion of the terminal region of chromosome 4 short arm and is frequently associated with intractable epilepsy. This article evaluates the clinical features of epileptic seizures in WHS and the therapeutic efficacy of oral antiseizure medications (ASMs). Patients with WHS who were treated for epilepsy at the Saitama Children's Medical Center under 5 years of age were included. WHS was diagnosed based on genetic tests and clinical symptoms. Medical records regarding the age of onset of epilepsy, seizure type, treatment of status epilepticus (SE), and effectiveness of ASMs were retrospectively reviewed. Oral ASMs were considered effective when seizures were reduced by at least 50% compared with the premedication level. Eleven patients were included in the study. The median age at the onset of epilepsy was 9 months (range: 5–32 months). Unknown-onset bilateral tonic-clonic seizure was the most common type of seizure, occurring in 10 patients. Focal clonic seizures occurred in four patients. Ten patients exhibited recurrent episodes of SE, and its frequency during infancy was monthly in eight patients and yearly in two. SE occurrence peaked at 1 year of age and decreased after 3 years of age. The most effective ASM was levetiracetam. Although WHS-associated epilepsy is intractable with frequent SE occurrence during infancy, improvement in seizure control is expected with age. Levetiracetam may be a novel ASM for WHS.
Keywords: chromosomal abnormality; status epilepticus; thermal hypersensitivity; novel antiseizure medications